Evaluasi Kinerja Pelayanan Publik Dalam Mewujudkan Good Governance di Kecamatan Asemrowo - Reza Maharani Putri Tizaka; Achluddin Ibnu Rochim (Jurnal Relasi Publik, 2024)
. his investigate points to assess the execution of open administrations in Asemrowo Area with a center on accomplishing great administration. Through subjective clear strategies, information is collected through interviews, documentation and observation. Evaluation of employee performance is carried out to ensure service quality meets established standards and achieves good governance. The research results show that public services in Asemrowo District are running well, supported by fast responses and the implementation of an online-based service system. Supporting factors include clear regulations and employee discipline, while inhibiting factors include low human resource competency and limited number of employees. Suggestions for improving public services include increasing awareness of performance evaluation, developing HR competencies, and increasing the number of employees as needed.